The Analysis of Desistance Driving Factors in the Perpetrators of Sexual Crimes - Yuli Kurniawaty (Universitas Budi Luhur, 2022)
Sexual crime is a form of crime that has a low victim record because of the tendency for victims not to report the incidents they have experienced. In fact, the psychological condition of victims of sexual crimes can be disrupted because they have to feel pain, wounds, hurt because of the physical attacks they receive. Meanwhile, perpetrators of sexual violations have a tendency to complete their actions. This condition should be overcome to prevent more victims from falling. Law enforcement is one form of effort to prevent the emergence of recidivism of sexual crimes in Indonesia. The form of chemical castration is an aggravating form of punishment for perpetrators of sexual crimes. However, it is widely assumed that this form of punishment does not guarantee a deterrent effect. This article uses the theory of desistance to criminal behavior which aims to determine the factors that influence a person not to repeat his actions again. This article argues that depending on six factors, namely age, stable employment, military service, juvenile detention, education, and fear of serious assault or death does not always guarantee the persistence of sex offenders.